Who's up to the challenge? 53

Calculus Level 5

0 1 ( ln x ) 2 Li 3 ( x ) 1 x d x = ( ζ ( b ) ) a ζ ( c ) \large \int_0^1 \dfrac{ (\ln x)^2 \; \text{Li}_3 (x)}{1-x} \, dx = (\zeta(b))^a - \zeta (c)

If the equation above holds true for positive integers a , b a,b and c c , find a + b + c a+b+c .

Notations :

  • ζ ( ) \zeta(\cdot) denotes the Riemann zeta function .
  • Li n ( a ) { \text{Li} }_{ n }(a) denotes the polylogarithm function, Li n ( a ) = k = 1 a k k n . { \text{Li} }_{ n }(a)=\displaystyle\sum _{ k=1 }^{ \infty }{ \frac { { a }^{ k } }{ { k }^{ n } } }.


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
May 9, 2016

Note that 0 1 x α 1 ( ln x ) 2 1 x d x = lim β 0 2 B α 2 ( α , β ) = ψ ( 2 ) ( α ) \int_0^1 \frac{x^{\alpha-1} (\ln x)^2}{1-x}\,dx \; = \;\displaystyle \lim_{\beta\to0}\frac{\partial^2B}{\partial\alpha^2}(\alpha,\beta) \; =\; -\psi^{(2)}(\alpha) for α > 0 \alpha > 0 , so that 0 1 x n ( ln x ) 2 1 x d x = ψ ( 2 ) ( n + 1 ) = 2 [ ζ ( 3 ) H n ( 3 ) ] \int_0^1 \frac{x^n (\ln x)^2}{1-x}\,dx \; = \; -\psi^{(2)}(n+1) \; = \; 2\big[\zeta(3) - H^{(3)}_n\big] for all integers n 1 n \ge 1 . Hence 0 1 ( ln x ) 2 L i 3 ( x ) 1 x d x = n = 1 0 1 x n ( ln x ) 2 n 3 ( 1 x ) d x = 2 n = 1 ζ ( 3 ) H n ( 3 ) n 3 = 2 [ ζ ( 3 ) 2 n = 1 H n ( 3 ) n 3 ] = 2 [ ζ ( 3 ) 2 1 2 ( ζ ( 3 ) 2 + ζ ( 6 ) ) ] = ζ ( 3 ) 2 ζ ( 6 ) \begin{array}{rcl} \displaystyle \int_0^1 \frac{(\ln x)^2 \mathrm{Li}_3(x)}{1-x}\,dx & = & \displaystyle \sum_{n=1}^\infty \int_0^1 \frac{x^n (\ln x)^2}{n^3 (1-x)}\,dx \; =\; 2\sum_{n=1}^\infty \frac{\zeta(3) - H^{(3)}_n}{n^3} \\ & = & \displaystyle 2\left[\zeta(3)^2 - \sum_{n=1}^\infty \frac{H^{(3)}_n}{n^3}\right] \; = \; 2\left[ \zeta(3)^2 - \tfrac12\big(\zeta(3)^2 + \zeta(6)\big)\right] \\ & = & \displaystyle \zeta(3)^2 - \zeta(6) \end{array} making the answer 2 + 3 + 6 = 11 2+3+6 = \boxed{11} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...